Method of surgical treatment of chronic dacryocystitis and its effectiveness in monitoring patients in the early postoperative period - Zabolotnyi, Dmytro; Minaiev, Oleksii (ScienceRise: Medical Science, 2021)
The aim. To develop a method for endonasal endoscopic dacryocystorhinostomy (EEDCR) and evaluate its effectiveness in monitoring patients in the early postoperative period. Materials and methods. The study group (1st group) consisted of 45 patients with chronic dacryocystitis (CD), who underwent EEDCR according to the developed method, the comparison group (2nd group) included 36 patients who, after performing the developed EEDCR, an implant was installed in the dacryorhinostoma zone. The control group (3rd group) included 28 patients who underwent EEDCR according to the generally accepted method. Patients of groups 1 and 2 were divided into 2 subgroups: 1A and 2A included patients who underwent computed tomography of the lacrimal ducts in the preoperative period according to the developed method, and patients of subgroups 1B and 2B – according to the traditional algorithm. Reliably the best results of restoring lacrimation function were in subgroups 1A and 1B already from the 3rd day of observation after surgery, as well as in the subsequent periods of observation. The worst values of lacrimation function were recorded in the control clinical group with a statistically significant difference from other groups (p<0.05). When comparing the results of treatment of subgroups 1A with 1B and 2A with 2B, the best indicators were observed in subgroups 1A and 2A, but due to the small sample of patients, statistical significance in the differences could not be achieved (p>0.05). Results. A method of EEDCR has been developed, a comparative analysis of groups of patients according to the above indicators has been performed when observing patients in the early postoperative period. On the first day after surgery, the mean score of the severity of lacrimation according to the Munk scale significantly decreased in all groups and gradually decreased on the 7th day and after 2 weeks (p<0.05). Significantly better indicators were in subgroups 1A and 1B in the entire early postoperative period (p<0.05). The degree of edema of the mucosa of the dacryorhinostoma zone and the middle nasal meatus at all periods of observation was the lowest in subgroup 1A from 3rd day and in each subsequent period of observation with a statistically significant difference from other groups (p<0.05). On the 7th day, significantly more patients with mucous discharge in the area of dacryorhinostoma and middle nasal meatus were observed in subgroup 2B and in 3rd group (p<0.05), and significantly better results were noted in subgroup 1A, where more than 2/3 patients had no mucous discharge. Reliably the best results of restoring lacrimation function were in subgroups 1A and 1B already from the 3rd day of observation after surgery, as well as in the subsequent periods of observation. The worst values of lacrimation function were recorded in the control clinical group with a statistically significant difference from other groups (p<0.05). When comparing the results of treatment of subgroups 1A with 1B and 2A with 2B, the best indicators were observed in subgroups 1A and 2A, but due to the small sample of patients, statistical significance in the differences could not be achieved (p>0.05). Conclusions. The developed EEDCR method complies with the principles of sparing surgery, is effective in the treatment of patients with CD, while there is a faster rate of recovery of the lacrimal function and mucosa, improves the quality of life of patients